2022
DOI: 10.1140/epjc/s10052-022-10109-2
|View full text |Cite
|
Sign up to set email alerts
|

Bianchi type I cosmology with a Kalb–Ramond background field

Abstract: An effect of the Lorentz symmetry breaking is pointed out in the cosmological context. Using a Bianchi I geometry coupled to the Kalb–Ramond field, a consequence of the Lorentz symmetry violation is indicated by a different rate of expansion in a given spatial direction. This article focuses on the coupling constant $$\xi _1$$ ξ 1 , which generates, from the Kalb–Ramond field, all three coefficients that give rise to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…46 Inspired by the Standard Model Extension (an effective field theory containing all possible Lorentz breaking operators in addition to the Standard Model and GR Lagrangian terms [761][762][763]) and by heterotic string theory [760], considered a scenario where the Kalb-Ramond field acquires a non-vanishing vacuum expectation value (VEV) b µν (with b 2 = b µν b µν ), as well as a non-minimal coupling to the Ricci tensor with strength ξ 2 (for the full action of the theory, see [760]). The non-zero VEV spontaneously breaks Lorentz invariance, leading to a host of interesting observational signatures [764][765][766].…”
Section: Kalb-ramond Black Holementioning
confidence: 99%
“…46 Inspired by the Standard Model Extension (an effective field theory containing all possible Lorentz breaking operators in addition to the Standard Model and GR Lagrangian terms [761][762][763]) and by heterotic string theory [760], considered a scenario where the Kalb-Ramond field acquires a non-vanishing vacuum expectation value (VEV) b µν (with b 2 = b µν b µν ), as well as a non-minimal coupling to the Ricci tensor with strength ξ 2 (for the full action of the theory, see [760]). The non-zero VEV spontaneously breaks Lorentz invariance, leading to a host of interesting observational signatures [764][765][766].…”
Section: Kalb-ramond Black Holementioning
confidence: 99%
“…Here, µναβ is the well known Levi-Cevita symbol, which is for Minkowskian spacetime equal to unity if it's indices are an even permutation of (1234), equal to −1 if indices are odd permutation of (1234) and vanish if one of the indices repeat. For KB field, stress-energy-momentum tensor reads [50]:…”
Section: Minimally Coupled Massless Kalb-ramond Fieldmentioning
confidence: 99%
“…B µν where is the antisymmetric rank 2 tensor, namely the Kalb-Ramond field. For the KB field, we have a set of two EoMs expressed as follows [47][48][49]:…”
Section: Minimally Coupled Massless Kalb-ramond Fieldmentioning
confidence: 99%
“…Apart from the massless representation of the Lorentz group, the KR field also arise as closed string mode [67], and are of considerable interest, in the context of String theory. Recently the possible roles of Kalb-Ramond field (coupled to Bianchi-I geometry) in the Lorentz symmetry violation has been studied in [68]. In the arena of higher dimensional braneworld scenario or in higher curvature gravity theory, it has been shown that the KR coupling (with other normal matter fields) gets highly suppressed over the usual gravity-matter coupling, which explains why the KR field has negligible footprints at the present universe [69][70][71].…”
Section: Introductionmentioning
confidence: 99%